Kilka uwag o bezcennych świadectwach kulturowego dziedzictwa ludowego zwerbalizowanych w dwutygodniku "Polskie Stroje Ludowe" z lat 2012-2013 (refleksje dialektologa-lingwokulturologa) = A few remarks on priceless testimonies of the cultural folk legacy verbalized in biweekly magazine "Polskie Stroje Ludowe" between 2012 and 2013 (reflections of a dialectologist-linguaculturologist) - Węgorowska, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The topic of the reflections is the timeless cultural content included in the folkloristic magazine patronized by State Folk Group of Song and Dance "Mazowsze". Folk artifacts, regional artists, institutions and organizations saving the countryside culture from falling into oblivion, specificity of native dialects and subdialects, creators and scholars inspired by the legacy of Polish peasants are some of the many topics/issues discussed in the periodical. Because of them its authors verbalized timeless values of folklore, which, despite changes in the outside reality, continues as an integral constitutive component of the native national tradition.
Keywords: werbalizacja; kultura ludowa; tradycja; wartości; wartościowanie; verbalization; folk culture; tradition; values; evaluation